2007
DOI: 10.1111/j.1468-0327.2007.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Age, seniority and labour costs: lessons from the Finnish IT revolution

Abstract: "The bad labour market performance of the workforce over 50 indicates that an aged workforce is often a burden for firms. Our paper seeks to investigate whether and why this is the case by providing evidence on the relation between age, seniority and experience, on the one hand, and the main components of labour costs, namely productivity and wages, on the other, for a sample of plants in three manufacturing industries ('forest', 'industrial machinery' and 'electronics') in Finland during the IT revolution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…Since individual-level productivity measures are available only in very special cases, a field of research has emerged, where linked employer-employee data sets are used for analyzing the impact of work force characteristics, like average age or shares of employees in different age groups, on plant-or firm-level productivity and wage (e.g. Hellerstein et al, 1999;Hellerstein & Neumark, 2004;Daveri & Maliranta, 2007). A drawback of this line of studies is that they do not pay much attention to how the structure of the work force is determined, although in some studies the work force age (and other characteristics) have been instrumented (Aubert & Cré-pon, 2003;Malmberg et al, 2005;Daveri & Maliranta, 2007).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Since individual-level productivity measures are available only in very special cases, a field of research has emerged, where linked employer-employee data sets are used for analyzing the impact of work force characteristics, like average age or shares of employees in different age groups, on plant-or firm-level productivity and wage (e.g. Hellerstein et al, 1999;Hellerstein & Neumark, 2004;Daveri & Maliranta, 2007). A drawback of this line of studies is that they do not pay much attention to how the structure of the work force is determined, although in some studies the work force age (and other characteristics) have been instrumented (Aubert & Cré-pon, 2003;Malmberg et al, 2005;Daveri & Maliranta, 2007).…”
Section: Previous Researchmentioning
confidence: 99%
“…Hellerstein et al, 1999;Hellerstein & Neumark, 2004;Daveri & Maliranta, 2007). A drawback of this line of studies is that they do not pay much attention to how the structure of the work force is determined, although in some studies the work force age (and other characteristics) have been instrumented (Aubert & Cré-pon, 2003;Malmberg et al, 2005;Daveri & Maliranta, 2007).…”
Section: Previous Researchmentioning
confidence: 99%
“…The significant negative effect of age seems striking at first glance. Most empirical studies investigating the age-earnings profile find a concave pattern suggesting a positive age effect for early and mid-career workers (e.g., Daveri and Maliranta (2007);Haltiwanger, Lane, and Spletzer (1999)). However, note that by focusing solely on persons graduating from university in the same year, we implicitly introduce a restriction for potential work experience after graduation, and those graduating at an older age might have needed more time to obtain their degree.…”
Section: Main Results On the Information Value Of Central School Examsmentioning
confidence: 99%
“…First of all, research on the relationship between age and productivity, whether measured at the individual level or at the organizational level, does not allow one to draw firm conclusions about a drop of productivity in older age. Metaanalysis and extensive literature reviews indicate that although the age effect is sometimes observed it is not always significant; in many cases it does not occur at all, whereas some research shows an increase in performance in older groups (McEvoy and Cascio 1989;Sturman 2003;Daveri and Maliranta 2007;Hellerstein, Neumark 2007;Ng, Feldman 2008). Age-productivity relationships cannot be easily generalised.…”
Section: Productivitymentioning
confidence: 98%